Analisis Faktor-Faktor yang Berpengaruh terhadap Kinerja Karyawan dan Implikasinya kepada Kesadaran Karyawan untuk membayah PPH - Entoh Sumaryo (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
Human resources (HR) is one key factor in global competition, creating quality and have the skills and highly competitive it is necessary. The government is attempting to realize this by issuing the policy on income tax and employee income tax in particular is expected, it will improve performance and motivation among employees to compete can do better. The core of this study to assess the influencing of motivation, competitiveness, discipline, understanding and awareness of compliance in implementing the Income Tax Employees against peformance.This study is a description of survey research. Papulasi of this study were all employees working at company option bonded zone while the sample in this study were employees who worked at the company's choice of the bonded zone by proportional clustrer sampling technique. The data collected were then tested with Pearson correlation statistical tests.’ Techniqueanalyses were used path analyisis. The results obtained for the motivation variable, competencies variabel, the work discipline variable againt employee performance are on positif; and also the performance employee and understandingon tax rulled againtemployee givepositif awareness in implementing the Employee Income Tax compliance.Based on the processing, analysis and discussion of data from the variables of motivation, competence, discipline, and understanding tax regulations related to its effect on performance, as well as the awareness of employees to pay income tax (PPh.). Get the highest criteria of good and excellent is not it a relationship between variables have a positive or interconnected relationships.